A New Approach in a New World: Education of Excellence for the Professionals of the Future (GESTIÓN Y TENDENCIAS, 2024)
Gestión y Tendencias (GESTEN) has, since its creation in 2015, been the outreach publication of the Department of Management and Business of the School of Economics and Business at Universidad Alberto Hurtado (FEN UAH).
Keywords: gesten; gestion y tendencias; education of excellence; professionals of the future